Phenomenology on Kant, German Idealism, Hermeneutics and Logic
VI, 356 p.
Keywords: Joseph 1. Kockelmans Pennsylvania State University In July of 1999, Prof. Dr. Thomas M. Seebohm turned 65 years old, and thus en tered mandatory retirement. His friends, colleagues, and former students thought that it would be fitting to celebrate the event of his retirement with a volume of essays in his honor, in order to render homage to a great human being, an outstanding and dedicated teacher, a highly regarded philosopher and scholar, but above all a dear friend and colleague. When the editors thought about a unifying theme for the anthology, they finally settled on the research interests of Professor Seebohm; in their view the vast do main of his competence and interests would leave all participants the freedom to select a topic of their own choice that would nonetheless lie within this large realm as well as within the area of their own research interests. Professor Seebohm's research interests encompass work in Phenomenology, Hermeneutics, German Idealism (Kant in particular), History of Philosophy, Phi losophy of the formal sciences (of Logic in particular), Philosophy of History, Methodology and Philosophy of the Human Sciences, (including Psychology and Sociology), History of 19th Century British Empiricism (Mill), American Pragma tism, Analytic Philosophy, Philosophy of Law and Practical Philosophy, the devel opment of the history of philosophy in Eastern Europe, especially in the Middle Ages, but also in the nineteenth century.